CURRENT STATUS AND IMPACT OF RECYCLING IN REPUBLIC OF SERBIA - Stojanović, Marija; Sokić, Miroslav; Jovanović, Aleksandar (Veredas do Direito, 2026)
One of the biggest challenges of modern society is the management of spent and discarded materials. Due to the continuous growth of the world’s population, waste generation is steadily increasing. The aim of this paper is to present the current state of the art of recycling in the Republic of Serbia, emphasizing the importance of understanding the basic elements of waste management. The implemented laws and regulations in the field of waste management provide a solid foundation for further progress in this area of environmental protection. The primary stages of proper waste management include: (1) generation, (2) collection, (3) sorting, (4) transportation and distribution, and (5) treatment or disposal. Selecting an effective solid waste treatment process remains challenging due to the variability and composition of input materials. In 2024, a total of 8.15 million tonnes (Mt) of waste was generated in the Republic of Serbia, of which 0.11 Mt was classified as hazardous. Therefore, appropriate waste management represents one of the most important components of a functional green economy, promoting environmental protection and the social sustainability of local communities.